Pengaruh Influencer dan Online Customer Review terhadap Keputusan Pembelian Produk Body Lotion Scarlett Whitening (Studi Kasus pada Masyarakat Generasi Z Kecamatan Medan Sunggal) - Tarisya Fitri Nabillah; Muhammad Yamin Siregar Siregar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to determine and analyze influencers and online customer reviews have a positive and significant partial effect on purchasing decisions, and to determine influencers and online customer reviews have a positive and significant simultaneous effect on purchasing decisions for Scarlett Whitening Body Lotion products in Generation Z Community in Medan Sunggal District. The population in this study was 22,086 female Generation Z community in Medan Sunggal District. The sample in this study was 100 consumers taken using the Slovin formula. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The results showed that influencers and online customer reviews had a positive and significant partial effect on purchasing decisions and influencers and online customer reviews had a positive and significant effect on purchasing decisions for Scarlett Whitening Body Lotion products in Generation Z Community in Medan Sunggal District. These findings indicate that the credibility of influencers and positive customer reviews can increase consumer trust, thereby encouraging purchasing decisions. This research is expected to be a consideration for companies in developing effective digital marketing strategies through the use of influencers and managing online customer reviews to improve consumer purchasing decisions.